Comparative evaluation of the results of an immunocytochemical study of P16/Ki-67 coexpression in patients with cervical intraepithelial neoplasia associated with human papillomavirus - Tatiana V. Klinyshkova; Irina B. Samosudova; Mariia S. Buyan (IP Berlin A.V., 2021)
Aim. To evaluate the results of an immunocytochemical study of p16/Ki-67 double staining in the cervical epithelium of patients with cervical intraepithelial neoplasia (CIN) associated with high-risk human papillomavirus (HPVhr) in comparison with patients without cervical pathology. Materials and methods. The comparative study included the results of examination of 75 patients divided into 4 groups. Patients with CIN1 comprised the 1st main group (n=21), women with CIN2CIN3 the 2nd main group (n=26), the comparison group consisted of patients with latent HPV infection (n=15) and the control group (n=13). The average age of women with cervical HPV infection was 26.46.13 years. Methods of investigation: liquid cytology, colposcopic, histological examination; methods for determining HPVhr DNA; immunocytochemical examination for determining double staining of p16/Ki-67 markers, statistical analysis. Results. A positive p16/Ki-67 double staining test prevailed among patients with CIN (31.9%) compared to patients without cervical pathology (3.6%) (p=0.003) and correlated with the severity of colposcopic signs (rs=+0.397, p=0.0004). In the 1st main group of patients with verified CIN1 and in the comparison group of patients with latent infection, isolated cases of a positive test of double staining of p16/Ki-67 markers in the epithelium were recorded without significant differences between the groups (9.5 и 6.6%, p0.05). In the 2nd main group of patients with verified CIN2, CIN3, a positive test of double staining of p16 and Ki-67 was observed in every second case, dominating relative to the 1st group, the comparison group and the control group (p=0.003, p=0.005, р=0.001 respectively). In the control group, a negative double staining test was established in all cases. Conclusion. Every second patient with CIN2+ associated with HPVhr has a positive test of double staining of the cervical epithelium, with CIN1 it is observed in 9.5% of cases (p=0.003). Among patients with CIN1, there were no differences in the expression of p16/Ki-67 in epithelial cells compared to women without cervical pathology. The data of the immunocytochemical study of p16/Ki-67 in the cervical epithelium of HPVhr positive patients with CIN should be taken into account when choosing a differentiated management strategy.